Does the Tax System Encourage too much Education? - Annette Alstadsæter (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper provides an efficiency argument in favour of progressive labour income taxation. When the consumer faces a trade-off between investments in financial and human capital, a proportional comprehensive income tax tends to discriminate in favour of human capital investments. This effect is strengthened when education no longer is a pure investment, but also holds a direct consumption value. A comprehensive proportional income tax works as a tax subsidy on human capital investments, and it reduces the price of education as a consumption good. By introducing a progressive labour income tax, the efficiency distortion in the capital market may be partly neutralised.
Keywords: 330; dual income taxation; optimal income taxation; human capital investment; consumption value of education